Effect of Microstructure on Wear and Corrosion Performance of Thermally Sprayed AlCoCrFeMo High‐Entropy Alloy Coatings. Issue 9 (9th February 2022) - Nair, Rakesh Bhaskaran; Perumal, Gopinath; McDonald, André
Abstract : High entropy alloys (HEAs) represent a new class of advanced metallic alloys that exhibit unique structural features and promising properties. The potential benefit of HEAs, in conjunction with established thermal spray manufacturing technologies, can provide a practical approach to mitigate wear and corrosion. Equiatomic AlCoCrFeMo HEA were fabricated using cold‐spraying and flame‐spraying, aiming to investigate the effect of low‐temperature and high‐temperature responses to phase formations, microstructural evolution, and microhardness. The performance evaluation during abrasive damage and electrochemical corrosion were also investigated. Microstructural studies revealed that coatings with body‐centered cubic (BCC) phases, where oxides were found in the flame‐sprayed coatings during in‐flight deposition. Hardness of the flame‐sprayed coatings showed noticeably (5.78 ± 0.45 GPa) higher than to that of the cold‐sprayed coatings (3.6 ± 0.48 GPa). Lower wear rates were achieved for the flame‐sprayed coatings (compared to the cold‐sprayed coatings. Oxide formations in the flame‐sprayed coatings decreased its corrosion performance such that it was two times lower than that of cold‐sprayed coatings. The results show that the microstructural features of flame‐sprayed coatings, coupled with formation of oxide inclusions resulted in improved resistance to damage due to wear loading, but undermined resistance to electrochemical degradation. Abstract : Here in, cold sprayed high entropy alloy coatings show approximately two times higher corrosion resistance than flame‐sprayed coatings and stainless steel, respectively. Flame‐sprayed high entropy alloy coatings, on the other hand, exhibit lower wear rates due to high fraction of oxide phases.